Megatsunamis Induced by Volcanic Landslides in the Canary Islands: Age of the Tsunami Deposits and Source Landslides - Ferrer, Mercedes (2022)
Evidence for frequent, large landslides on the flanks of the volcanic edifices forming the Canary Islands include outstanding landslide scars and their correlative submarine and subaerial rock and debris avalanche deposits. These landslides involved volumes ranging from tens to hundreds of km3. The sudden entry of large volumes of rock masses in the sea may have triggered tsunamis capable of affecting the source and neighboring islands, with the resulting huge waves dragging coastal and seabed materials and fauna and redepositing them inland. Here, we present new geological evidence and geochronological data of at least five megatsunamis in Tenerife, Lanzarote, and Gran Canaria, triggered by island flank megalandslides, and occasionally explosive eruptions, during the last 1 million years. The exceptional preservation of the megatsunami deposits and the large area they cover, particularly in Tenerife, provide fundamental data on the number of tsunami events and run-ups, and allow proposals on the sources and age of the tsunamis. Tsunami run-up heights up to 290 m above coeval sea level, some of the highest known on Earth in recent geological times, were estimated based on sedimentological, geomorphological, paleontological, and geochronological data. The research results made it possible to estimate the recurrence of tsunamis in the archipelago during the last hundreds of thousands of years, and to establish relationships between tsunami deposits and the probable triggering island flank landslides.